2020
DOI: 10.1093/icvts/ivaa132
|View full text |Cite
|
Sign up to set email alerts
|

A systematic evaluation on reporting quality of modern studies on pulmonary heart valve implantation in large animals

Abstract: OBJECTIVES Before new heart valves can be implanted safely in humans, animal experiments have to be performed. These animal experiments have to be clearly designed, analysed and reported to assess the accuracy and importance of the findings. We aimed to provide an overview of the reporting and methodological quality of preclinical heart valve research. METHODS We conducted a systematic literature search on biological and mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 15 publications
2
3
1
Order By: Relevance
“…This study found an association between the average Essential 10 score and the journal assessed. This result contrasts with the study by Uiterwijk et al (2020), who did not find a significant correlation between agreement with the item and the 5-year impact factor of the journal in which the studies were published. Our finding that AAW journal showed significantly higher compliance scores than AAB and AW must be treated cautiously because of the differences in sample sizes.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This study found an association between the average Essential 10 score and the journal assessed. This result contrasts with the study by Uiterwijk et al (2020), who did not find a significant correlation between agreement with the item and the 5-year impact factor of the journal in which the studies were published. Our finding that AAW journal showed significantly higher compliance scores than AAB and AW must be treated cautiously because of the differences in sample sizes.…”
Section: Discussioncontrasting
confidence: 99%
“…This result is in accordance with other animal research studies. For example, Uiterwijk et al (2020) reported a high percentage of articles (94%) included information concerning ethical statements in studies of pulmonary valve implantations in animals. Ting et al (2015) found 22% of articles with no statement concerning ethics approval in animal studies in the field of experimental rheumatology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of all 148 studies that did not report on health/immune status of the animals, 59 studies were published before 2010, and 89 studies after 2010. A similar alarming conclusion was made in a systematic evaluation on reporting quality of the assessment of pulmonary heart valve prosthesis in large animals 62 . The authors concluded that the introduction of the ARRIVE guidelines did not improve reporting quality over the last 20 years in the field of heart valve research 62 .…”
Section: Discussionsupporting
confidence: 53%
“…A similar alarming conclusion was made in a systematic evaluation on reporting quality of the assessment of pulmonary heart valve prosthesis in large animals 62 . The authors concluded that the introduction of the ARRIVE guidelines did not improve reporting quality over the last 20 years in the field of heart valve research 62 . Of note, reporting of animal sex in the studies included in our review was much better after 2010, even though animal sex was not reported for 25% of all included animals (32% of all included studies).…”
Section: Discussionsupporting
confidence: 53%